Esl and tesl students' attitudes and perceptions on the importance of drama as a technique in teaching literature in esl classroom - Mabel, James Daim (Universiti Malaysia Sarawak, UNIMAS, 2009)
The aim of this study was to investigate the attitudes and perceptions of TESL and ESL students in Universiti Malaysia Sarawak (UNIMAS) on the importance of using drama as a technique in teaching literature in ESL classroom. It is also to determine TESL and ESL students’ understanding of drama, to identify the TESL and ESL students’ attitudes and perceptions on the importance of using drama, and to discover the challenges that TESL and ESL students might perceive in implementing drama and to locate the possible suggestions to overcome the challenges. 71 participants from TESL and ESL programme, Faculty of Cognitive Sciences and Human Development were involved in this study and data was collected through questionnaire. Data collected was analyzed by using SPSS 15.0.The findings of the study indicated that majority of the TESL and ESL students showed positive attitudes and perceptions towards drama. Majority of the students understand the main concepts of drama although some of the students have misconception in drama. The findings also indicated the challenges that TESL and ESL students might perceive in implementing drama whereas the challenge of time consuming was the major reason that caused them hesitate or uncertain to use this technique in teaching literature. A number of suggestions were requested from the respondents to overcome the problems.